(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Nanotechnology has emerged as a gift for mankind in a variety of areas of research and everyday life with huge potential. The application of nanotechnology in the creation of bio sensors results in a very effective Nano-biosensor with a tiny structure compared to conventional biosensors. nano sensors and smart delivering Nano-dynamic systems may be used to monitor the discharge of pest and pathogenic agrochemicals, to identify plant virus, to detect soil nutrient level, and to release slow release Nano-encapsulated fertilizer, without losing it via leaching. Consequently, there is great optimism that such robots may support agriculture by boosting output and productivity. In a wide variety of areas of research and in our everyday lives, nanotechnology has emerged as a gift for mankind. Because nanotechnology is utilized to improve biological sensors, it produces a more robust Nano-biosensor with a smaller structure. A wide variety of fertilizers, herbicides, pesticides, insecticides, microorganisms, moisture and soil pH may also be detected using Nano biosensors. Nano-biosensors may assist promote sustainable agriculture and improve crop production when utilized correctly and in a controlled way.